Saliva as a non-invasive tool for monitoring oxidative stress in swimmers athletes performing a VO2max cycle ergometer test - Biagini, D.; Lomonaco, T.; Ghimenti, S.; Fusi, J.; Cerri, E.; de Angelis, F.; Bellagambi, F. G.; Oger, C.; Galano, J. M.; Bramanti, E.; Franzoni, F.; Fuoco, R.; et al. (Talanta, 2020)
Highlights